Agriculture and climate change: The constructive role of international trade - Fischler, Franz (International Food Policy Research Institute, 2009)
An open and flexible global trading environment plays a constructive role in both climate change mitigation and adaptation. A new international climate change regime and global trade rules should ideally be mutually reinforceable.